An Analysis of Determinants of Open Unemployment in Riau Islands: Schooling, Growth, Minimum Wages, Gender - Okluanty, Fibi Nur; Bachtiar, Arief (Universitas Gorontalo, 2025)
This Study aims to analyze the effect of mean years of school, economic growth, regional minimum wage, and gender on the open unemployment rate in the Riau Islands Province. The research uses panel data from 7 regencies/cities during the period 2019 to 2024 obtainded from publications of Statistics Indonesia. The results indicate that mean years of school and economic growth have a significant negative effect on the open unemployment rate, the regional minimum wage has no significant effect, while gender has a significant positive effect. These findings highlight the improvements in educational attainment and economic growth can reduce the open unemployments rate, whereas the increasing participation of female labor needs to be balanced with inclusive job creation policies to prevent a rice in unemployment.